Properties of a kunitz-type trypsin inhibitor from delonix regia seeds against digestive proteinases of anagasta kuehniella (Z.) and corcyra cephalonica (S.) (Lepidoptera: Pyralidae) - Macedo, M. L.R.; Pando, Silvana Cristina; Chevreuil, Larissa Ramos; Marangoni, Sérgio (Protein and Peptide Letters, 2009)
DrTI was effective against trypsin-like enzymes from A. kuehniella and C. cephalonica, however an artificial diet was insufficient to affect the survival and body weight of either insect. The inhibitor stimulated chymotrypsin-like enzymes and probably induced the synthesis of enzymes insensitive to TLCK in neonate larvae. © 2009 Bentham Science Publishers Ltd.
Keywords: Kunitz Type Protease Inhibitor, Plant; Kunitz Type Protease Inhibitor, Plant; Peptide; Peptide Hydrolase; Serine Proteinase Inhibitor; Tosyllysyl Chloromethyl Ketone; Vegetable Protein; Animals; Chemistry; Drug Effect; Enzymology; Larva; Legume; Lepidoptera; Metabolism; Seed Plant; Animal; Fabaceae; Larva; Lepidoptera; Peptide Hydrolases; Peptides; Plant Proteins; Seeds; Serine Proteinase Inhibitors; Tosyllysine Chloromethyl Ketone; Anagasta Kuehniella; Corcyra Cephalonica; Delonix Regia; Fabaceae; Hexapoda; Lepidoptera; Pyralidae